PENDAMPINGAN PENYUSUNAN PROFIL DESA NGOKOMALAKO KECAMATAN KAYOA UTARA KABUPATEN HALMAHERA SELATAN - sahrul_posi, sahrul_posi (Fakultas Teknik, Universitas Bangka Belitung, 2023)
This community service activity was carried out in Ngokomlako Village, North Kayoa District. The purpose of this service is to provide knowledge and understanding to the village government about the importance of the Village Profile. The Village Profile is very much needed as a means of socializing and actualizing the potentials that exist in the village. The specific target to be achieved in this service is the compilation of the Ngokomalako Village profile. For this reason, training is needed to prepare a good and correct village profile so that the aims and objectives of making a village profile in making village development policies are in accordance with the needs of the community. This service method is using Forum Group Discussion (FGD). FGDs were conducted to obtain in-depth information related to village structure, village profile and village potential that had been carried out. In addition, this community service is also carried out by assisting in preparing village profiles. The participants in this activity were the village government, totaling 15 people. The results of the evaluation of community service activities show that the knowledge of the village government has increased in preparing village profiles. In addition, there has also been a change in understanding in collecting data on village profile needs.